The Influence of Digital Marketing, Brand Image, and Service Facilities on Customers’ Saving Interest Decisions (A Case Study of BSI Branch Office Gajah Mada) - Fairuz Firjatullah; Nur Ahmadi Bi Rahmani; Muhammad Latief Ilhamy NST (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
In this study, the aim was to determine the effect of digital marketing, brand image, and service facilities on customer interest, and retention (a case study of BSI Branch Office (KC) Gajah Mada). The type of research used in this research is quantitative research. The object of this research was carried out at BSI KC Gajah Mada. The population used in this study were 3,415 BSI KC Gajah Mada customers who saved at the bank in 2020- 2023. While the sample data was taken using the Slovin formula as many as 97 respondents. The authors’ data analysis technique uses Validity and Reliability tests, as well as multiple classical assumption tests such as normality, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. Based on the results of research conducted partially, shows that digital marketing, brand image, and service facilities have a significantly positive effect on customer interest in deposits at BSI KC Gajah Mada. The calculation of the F test shows that the Fcount value is 51.223 with a significant value of 0.000. Because the significance value (α) <0.05, namely 0.000 <0.05, and for the value of Fcount > Ftable, namely 46.904 > 2.70. So, it means that it can be stated that simultaneously all the independent variables have a significant positive effect on the dependent variable interest in making customers (Y). 05 and for the value of Fcount > Ftable, namely 46.904 > 2.70.